The estimation of body stature based on the tibial length among Acehnese population - Mulkan Mulkan (Universitas Syiah Kuala, 2011)
Abstract. The stature reconstruction is commonly predicted statistically among different populations. Among long bones, tibia has been opted to predict the body stature as it has given better correlation of coefficient (r) and coefficient of determination (r2). There were 117 Acehneses involved in the study. Both body stature and tibial length were measured. The results of study showed better r and r2 i.e. 0.81 and 0.66 respectively. The formula of stature estimation was Y = 88.63 + 2.14* tibia ± 3.01. The stature estimation showed insignificant difference (p 0.05) as compared to the actual body stature. The variation of body stature might be seen different among populations and nations throughout the world.